Growing United Upgrading Europe's Convergence Machine - Ridao-Cano, Cristobal (World Bank E-Library Archive, 2018)
Since its foundation over sixty years ago, the European Union (EU) has become the modern world's greatest "convergence machine", propelling poorer, and newer, member states to become high-income economies, and delivering to its citizens some of the highest living standards and lowest levels of income inequality in the world. But today, Europeans are increasingly recognizing that convergence is not automatic. Inequality among people has been mounting in many parts of the EU since the 1990s, as low-income Europeans are falling behind in the labor market. And the productivity gap between Southern and Northern member states has been widening since the early 2000s. The EU is growing, but Europeans are not "growing united". Why? Growing United argues that technological change, by revolutionizing product and labor markets, is slowing down the old convergence machine: technology offers ever richer opportunities for well-skilled workers and frontier firms, while low-skilled workers and less productive firms risk falling behind. As a result, countries that provide less opportunities for people to build relevant skills and a less supportive environment for firms to thrive are losing ground. This calls for an upgrade to Europe's convergence machine, to seize the benefits of technological change for all Europeans. Growing United argues that the convergence machine, version 2.0, should focus on the convergence of opportunities for people and firms across the Union. It should support the capabilities of people (skills) and firms (innovation), and provide a level-playing field for people and firms through "flexicure" labor markets and an enabling business environment